2015
DOI: 10.1007/s00122-015-2553-6
|View full text |Cite
|
Sign up to set email alerts
|

A simple model for pollen-parent fecundity distributions in bee-pollinated forage legume polycrosses

Abstract: A simple Weibull distribution based empirical model that predicts pollen-parent fecundity distributions based on polycross size alone has been developed in outbred forage legume species for incorporation into quantitative genetic theory. Random mating or panmixis is a fundamental assumption in quantitative genetic theory. Random mating is sometimes thought to occur in actual fact, although a large body of empirical work shows that this is often not the case in nature. Models have been developed to explain many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…There was, however, a significant positive linear relationship between a polycross's l and its 50th quantile estimated l from 169 polycross l estimates assuming a lognormal distribution 1.166 -1.090 -50th quantile estimated l from 169 polycross l estimates assuming a gamma distribution 1.189 -1.095 - † Estimated k value based on k = 0.1019l 5 − 0.9441l 4 + 3.4386l 3 − 6.2398l 2 + 5.7585l − 1.0662. distributions (Riday et al, 2015). The first relationship measured was between a polycross's l and its N. No significant linear relationship was determined (P = 0.295, r 2 = 0.007).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…There was, however, a significant positive linear relationship between a polycross's l and its 50th quantile estimated l from 169 polycross l estimates assuming a lognormal distribution 1.166 -1.090 -50th quantile estimated l from 169 polycross l estimates assuming a gamma distribution 1.189 -1.095 - † Estimated k value based on k = 0.1019l 5 − 0.9441l 4 + 3.4386l 3 − 6.2398l 2 + 5.7585l − 1.0662. distributions (Riday et al, 2015). The first relationship measured was between a polycross's l and its N. No significant linear relationship was determined (P = 0.295, r 2 = 0.007).…”
Section: Discussionmentioning
confidence: 93%
“…Using empirical measures of pollen-parent fecundity distributions in 10 forage legume polycrosses, k and l were estimated to be 1.126 and 1.524, respectively (Riday et al, 2015). Riday and Peel (2016) demonstrated that Eq.…”
Section: Seed-parent Fecundity Distributions In Bee-pollinated Foragementioning
confidence: 99%
See 3 more Smart Citations